Predictors of Insurance Claim Rejection in Hand and Upper Extremity Surgery. Issue 15 (1st August 2020) - Matson, Andrew P.; Earp, Brandon E.; Benavent, Kyra A.; Geresy, Katarina M.; Collins, Jamie E.; Blazar, Philip E.
Abstract : Introduction: Insurance claim rejections represent a challenge for healthcare providers because of the potential for lost revenue and administrative costs of reworking claims. Methods: The billing records of five hand and upper extremity surgeons at a tertiary academic center were queried for all patient billing activity over a 1-year period yielding a total of 14, 421 unique patient encounters. Results: A total of 11, 839 unique patient encounters were included, and the overall claim rejection rate was 19.3%. Claim rejection rate varied significantly by payer ( P < 0.0001) and was lowest in private insurance (14.0%) and highest in Medicare (31.2%). The use of multiple Current Procedure Terminology codes for an encounter was independently associated with an increased risk of claim rejection for both office (25.6%, relative risk [RR] 1.27, 95% confidence interval [CI] 1.03 to 1.49, P = 0.0032) and surgical (25.6%, RR 1.67, 95% CI 1.28 to 2.18, P = 0.0002) settings. After multivariate regression adjustment, modifier 25 was associated with a decreased risk of claim rejection (23.3%, RR 0.72, 95% CI 0.61 to 0.85, P < 0.0001). Discussion: Insurance claim rejection occurs frequently (19.3%) in hand/upper extremity surgery and varies by insurance type, with the highest rejection rate occurring in Medicare (31.2%). For a given encounter, the use of multiple Current Procedure Terminology codes and specific modifiers are predictive of rejection risk. Level of Evidence: Level III, prognostic